THE CHEMISTRY OF SALINIZATION AND TRANSFORMATION OF THE CHEMICAL COMPOSITION OF SOILS AND RECLAIMED SOILS IN THE OIL FIELD - Tomina, Т.К. (Hydrometeorology and ecology, 2023)
Salinity of soils and contaminated soils the former oil pits in postresuscitational period ranges from medium degree to very strong. The predominant type of the chemism of salinity is sulphate-chloride, magnesium-calcium-sodium, and less chloride, sodium. The revealed transformation of the chemical composition of soils on reclaimed sites under the influence of new techniques of remediation in the process of recovery in the initial soil in arid conditions.